Molecular self-assembly of copolymer from renewable phenols: new class of antimicrobial ointment base. Issue 18 (12th December 2018) - Mahata, Denial; Mandal, Santi M.
Abstract: Ointments are highly viscous forms intended for external applications either medicated or non-medicated means. Formulation of ointment depends upon the base ingredients to measure the viscosity difference. Several limitations of ointment bases has been encountered timely as agglomeration, oil phase ingredients can form lumps, poor dispersion, poor drug delivery efficiency, make stained, immiscible, and difficult to wash off. Therefore, it is necessary to make a new type of ointment bases that can overcome those limitations. This review summarizes a new type of ointment base preparation from the copolymer of renewable phenolic derivatives. The nanohydrogel preparation from these copolymers are especially effortless and highly efficient in drug delivery, exhibited versatile biological activities such as antioxidant, anti-inflammatory and wound healing in addition to antimicrobial property. Molecular self-assembly mechanisms have been addressed for nanogel formulation. The strategy makes a significant value in health-care application and be supposed to come marketed soon.